English Master’s Students’ Idiomatic Expressions Understanding: Effect of Gender, Causes of Difficulties and Learning Strategies - Arifuddin Arifuddin; Henny Soepriyanti (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: Many Master’s students in English Language Education struggle to achieve the minimum TOEFL score. However, limited research has explored how gender influences their understanding of idioms. This study examined: (1) students’ idiomatic understanding by gender; (2) gender effects on idiom comprehension; (3) causes of difficulty; and (4) learning strategies used. Methodology: A mixed-methods design involving 212 English Master’s students. Data were collected with tests, questionnaires, and interviews. Descriptive statistics were used to assess students’ idiom comprehension levels, and the Pearson Product-Moment Correlation was used to assess the relationship between idiom comprehension and other variables. For stages of qualitative analysis - data reduction, data display, and conclusion drawing – were applied. Main Findings: The study reveals a medium level of idiomatic competence and no significant gender effect—challenging prevailing assumptions of gendered pragmatic advantages. Key difficulties include limited exposure to authentic input, unfamiliarity with figurative meaning, infrequent reading, and forgetfulness. Students rely on strategies such as reading idiom materials, using dictionaries, making contextual inferences, and using multimedia. Novelty/Originality of this study: The main challenges stem from limited exposure, literal interpretation, and insufficient cultural and contextual knowledge. Nevertheless, students demonstrated learner autonomy by employing diverse strategies such as using idiom dictionaries, engaging with authentic media, and contextual guessing. The study offers ‘novel’ insights for integrating idiomatic instruction to enhance postgraduate pragmatic competence and TOEFL outcomes.